Dukungan Keluarga dan Kualitas Hidup Pasien Diabetes Mellitus yang Berobat di Puskesmas - Muhammad Jais; Teuku Tahlil; Suryane Sulistiana Susanti (Jurnal Keperawatan Silampari, 2021)
This study aims to examine the relationship between family support and the quality of life of DM patients. This type of research is a quantitative research using a cross-sectional design. The results showed that most DM patients (64.3%) had a good quality of life. There is a statistically significant relationship between the quality of life of patients with emotional support (p-Value = 0.0002), instrumental (p-Value = 0.0005), and informational (p-Value = 0.000), but the relationship is not significant with support award (p-Value = 0.52). In conclusion, factors related to the quality of life of DM patients are emotional, instrumental, and informational support. Keywords: Diabetes Mellitus, Family Support, Quality of Life